(untitled) (Academia Journal of Medicine, 2018)
Background: Chronic renal failure (CRF) is characterized by irreversible destruction of nephrons along with decrease glomerular filtration and suppressed urine. Disturbance of lipid profile in CRF has been found associated with increased triglycerides (TG) and low high density lipids while normal level of total cholesterol (TC) and low density lipids (LDL). Dislipidemia in CRF patients induces cardiovascular diseases (CVD); in addition, CVD in turn leads to more rapid destruction of kidney. Therefore the present study was designed to evaluate the lipid profile in CRF patients with and without dialysis. Subjects and Methods: This was a prospective type of study conducted in the department of medicine of a tertiary care centre. Total 100 patients of CRF patients and 40 normal control subjects were recruited for the study. CRF patients were divided into two groups. Group I consisted CRF patients with dialysis and group II included CRF patients without dialysis. Normal subjects were kept under group III control group. Results: Results of the present study revealed that there was a significant difference between TG, HDL and VLDL of group I (p>0.01) and group II (p>0.01) in comparison of group III. Nevertheless, there was no significant difference between the TC and LDL of all groups. Conclusion: CRF patients either with dialysis or without dialysis have a great possibility of developing dyslipidemia as well as CVD. Dialysis has been found effective in reducing nitrogenous waste products in blood; however, it is not able to decrease lipid profile in CRF patients.